OPTIMALKAN KESEHATAN KELUARGA: PENDAMPINGAN TPK DALAM PENINGKATAN GIZI DAN PENCEGAHAN STUNTING DI DESA KELAMBIR KABUPATEN DELI SERDANG - Hodriani, Hodriani; Rahmi, Anna; Hadiningrum, Sri; Listia, Wan Nova; Junaidi, Junaidi (Jurnal Abdi Insani, 2024)
Deli Serdang Regency is a stunting locus area in North Sumatra. One of the 45 stunting locus villages in Deli Serdang Regency is Kelambir Village which is located in Pantai Labu District. Kelambir Village has formed a KPM management structure which has an important role in fostering stunting prevention, which activities are carried out to prevent stunting to fulfill nutritional needs for toddlers and pregnant women. This mentoring activity aims to fulfill community nutrition, especially those at risk of stunting, gaining knowledge and skills in providing healthy food and nutritious food based on local resources and improving family welfare. The method for this activity is an approach to partners and then implementation which includes education, outreach, training and assistance in creating a healthy menu to prevent stunting. The results of the activities show the positive impact of this socialization and mentoring. Activity participants, both from the PKK team, prospective brides and grooms, pregnant women and mothers with children under five can understand the use of local food as a healthy kitchen menu to prevent stunting. Positive results from the evaluation will indicate that participants have been able to internalize this information and apply it in the context of everyday life. Utilizing local Indonesian food is not just a culinary innovation, but is also a sustainable strategy to meet the nutritional needs of pregnant women and children under five. This activity is expected to be able to create a healthy eating environment, a synergistic relationship between the environment, local economy and public health.